MANUSKRIP AL-QUR’AN DI THAILAND SELATAN - Akbar, Ali (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
Southern Thailand is a strong Muslim community that strongly preserves its Islamic tradition. The intellectual heritage of Islam, including copies of the ancient Qur'an manuscripts are available in Islamic boarding school (pondok) and the settlements around the old mosque—and lately are also available in the museum. The tracing of Qur'an manuscripts in Southern Thailand seems to have never been done before. This article traces three places of the collection of Qur'an manuscripts in the museums and the communities such as in the Qur'an Museum and the Old Manuscripts in Narathiwat, Telok Manok Mosque, and Bankuanlangnga Mosque, Pattani. Based on the information from the fieldwork, there was a migration of the Qur'an manuscripts—besides other religious texts—since the 1980s out of the Southern Thailand, and now those manuscripts become collection of several public and private institutions especially in Malaysia and Brunei. On the contrary, lately, since the establishment of the Qur'an Museum in Narathiwat, there has been an attempt to return a number of manuscripts of the Qur'an to Southern Thailand. However, as seen from the new collection at the Qur’an Museum, most of the manuscripts of the Qur'an are from Java, and not the original manuscripts of the Qur’an from Southern Thailand.